PERANAN HEART RATE TERHADAP KUALITAS CITRA PADA PEMERIKSAAN CT ANGIOGRAPHY CARDIAC - Susanti, Titin; Arinawati, Arinawati; Sulaksono, Nanang (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Cardiac angiography CT examination is a non-invasive measure to evaluate coronary blood vessels. Multislice CT with a high level of sensitivity and specificity is required to be able to reconstruct data from a constantly moving heart, resulting in diagnostic and informative image quality. Heart movement or heart rate plays a role in the occurrence of motion artifacts so that a stable heart rate is required at the time of data acquisition. The purpose of this paper is to see the role of the heart rate in cardiac CT Angiography examination and to determine the value of the heart rate to obtain the best image quality. Methods: The research method uses a literature study approach by describing the article. Article searches use Science Direct, Radiopedia, American Journal Radiography, and Google Search to find articles that match inclusion and exclusion criteria so that 4 articles are obtained and then they are reviewed. Results:: The study results show that the heart rate plays a very important role in producing image quality from CT examination. Cardiac angiography, a stable heart rate will minimize the occurrence of artifacts, which is one of the points in the image quality parameter. A stable heart rate to get the best image quality is at â‰¤60 BPM when data acquisition with low heart rate variability Conclusion: .Nilai heart rate untuk mendapatkan kualitas citra yang informatif dan diagnostik pada nilai heart rate 60 bpm, sehingga kualitas citra akan baik.